The prevalent life cycle of agricultural flash droughts - Lovino, Miguel Angel (2024)
This work examines the characteristics and prevalent life cycle of agricultural flash droughts globally.Using ERA5 data, the study introduces a flash drought indicator based on soil water availability. Thisapproach integrates root-zone soil moisture and hydraulic soil properties, such as field capacity andwilting point, to couple the rapid soil moisture depletion and plant water stress. Our findings reveal thatagricultural flash droughts present their higher frequency predominantly during the critical growthperiods of crops. Notably, these droughts exhibit a similar life cycle regardless of the location orclimatic regime. The primary cause of the rapid soil moisture depletion is the precipitation deficit, butevapotranspiration also plays a significant role. In an energy-limited environment, evapotranspirationrapidly increases before the onset and decreases rapidly during the intensification period as thesystem becomes water-limited. Upon concluding the intensification period, most crops experiencewater stress, diminishing their yields.